UJI DAYA HAMBAT EKSTRAK DAUN TUMBUHAN Harrisonia perforata (BLANCO) MERR. TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Fitri Maija; Orryani Lambui; Ramadhanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2016)
Research of inhibition test from the leaves extract of Harrisonia perforata (Blanco) Merr. on the growth of Staphylococcus aureus was carried out in February and March 2015. This study was aimed to determine the effectiveness of the leaves extracts from H. perforata (Blanco) Merr. for inhibiting the bacterial growth. The extraction used maceration methods and the inhibition assay from the extracts for S. aureus used wells diffusion method. The treatment was arranged in Completely Randomized Design (CRD) with 6 treatments and 3 replications. Concentration for this treatment leaves extract were 10%, 25%, 40%, and 65%, amoxicillin 2% as a positive control and NA-CMC 1% as a negative control. The results showed that the concentration leaves extract of 65% formed the highest in inhibition zone, which was 19,3 mm. It means that the leaves extract of H. perforata (Blanco) Merr. was better to inhibit the bacterial growth. Keywords : Leaves extract, Harrisonia perforata (Blanco) Merr., Staphylococcus aureus.